2023
DOI: 10.3390/coatings13061036
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Wet and Dry Treatments on Surface Functional Groups and Mechanical Properties of Flax Fiber Composites

Abstract: Flax fibers have found widespread use in eco-composite materials because of their remarkable mechanical properties compared to glass fibers. However, their low stability limits their use on a larger scale when employed in hot or humid environments. Therefore, the surfaces should be modified before the composite process to provide the best interfacial interactions and increase the dispersion of natural fibers. To tackle this problem, two kinds of modifications can be considered: wet and dry modifications. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 43 publications
3
5
0
Order By: Relevance
“…The smoother appearance observed at high magnitude indicates that the plasma treatment has effectively modified the surface characteristics of the fibres. These findings align with our previous research [28] on the impact of plasma treatment on the removal of natural waxy substances from the fibres, indicating the treated state of the samples. Thus, the results reinforce the efficacy of plasma treatment to replace conventional wet methods to "clean" and/or functionalize the surface of natural fibres in dry conditions.…”
Section: Comparative Images Of Flax Fibers Pre and Post Treatmentssupporting
confidence: 93%
See 3 more Smart Citations
“…The smoother appearance observed at high magnitude indicates that the plasma treatment has effectively modified the surface characteristics of the fibres. These findings align with our previous research [28] on the impact of plasma treatment on the removal of natural waxy substances from the fibres, indicating the treated state of the samples. Thus, the results reinforce the efficacy of plasma treatment to replace conventional wet methods to "clean" and/or functionalize the surface of natural fibres in dry conditions.…”
Section: Comparative Images Of Flax Fibers Pre and Post Treatmentssupporting
confidence: 93%
“…Upon subjecting the flax fibre to plasma treatment using N2 gas some transformations in the ATR-FTIR spectra were observed (zoom (a)). Remarkably, the characteristic peaks associated with wax at approximately 2915 cm −1 and 2850 cm −1 , which correspond to the asymmetrical and symmetrical stretching of CH2 groups, were effectively eliminated in agreement with previous findings [28]. In addition, the emergence of a distinct peak around 1720 cm −1 signified the presence of a carbonyl group (zoom (b)).…”
Section: Ftir Of Non-treated and Treated Flax Fibersupporting
confidence: 90%
See 2 more Smart Citations
“…In spinning processes, they reduce the coefficient of friction, facilitating the formation and thinning of a stream of parallelly arranged fibers [ 18 , 19 ]. Various methods of fiber processing lead to partial removal of waxes and fats, but may lead to better fiber adhesion [ 51 , 52 , 53 ]. The evaluation of the content of waxes and fats in the flax fiber of the MODRAN and NIKE variety showed that the degumming of the decorticated fiber caused the partial removal of waxes and fats in the fiber as a result of the combined action of water and ultrasound.…”
Section: Resultsmentioning
confidence: 99%